The Implementation of Preview, Question, Read, State, and Test for Teaching Reading in Junior High School - Anggita Pramestia Dewi, Ni Nyoman; Krismayani, Ni Wayan Krismayani; Agung Gana Kumara, Dewa Gede (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2024)
Reading is a skill that people should be familiar with regularly because it is the foundation of language. Readers can learn a lot by reading. Reading encourages the growth of critical thinking skills as well. It also helps people to learn words and pronunciation. The primary goal of this study is to implement Preview, Question, Read, State, and Test (PQRST) in teaching reading. The subject in this study is the eighth-grade students of SMPN 3 Abiansemal in the academic year 2023/2024. The class consisted of 31 students lacking reading comprehension, especially in finding the main idea, general and specific information, textual meaning, and references. The researchers used three tests to collect data: pre-test, post-test, and questionnaires. The researchers used the mean score formula when all subjects' pre-test and post-test data were calculated. The result of the questionnaire in this study used to find out and analyze the students' percentages of the subject responses to the techniques is applied.